Therapeutic drug monitoring in inflammatory bowel disease reduces unnecessary use of infliximab with substantial associated cost‐savings. Issue 5 (27th May 2021) - Wu, Yang; Lin, Brian; Thilakanathan, Cynthuja; Lehmann, Patritica; Xuan, Wei; Mohsen, Waled; Toong, Catherine; Williams, Astrid‐Jane; Ng, Watson; Connor, Susan
Abstract: Background: Therapeutic drug monitoring (TDM) of infliximab (IFX) levels in inflammatory bowel disease (IBD) patients can help to guide dose adjustments or changes to therapy for selected patients in remission or with secondary loss of response (LOR). Aims: To determine how IFX TDM is utilised in a real‐life clinical setting and to quantify the potential for TDM to reduce the unnecessary use of IFX. Methods: Data from all public IBD IFX level testing performed across Australia were prospectively collected from June 2016 to July 2017 to assess physician‐reported for testing indications (induction, in remission or LOR) and associated results. The hypothetical influence of IFX TDM was based on an optimal therapeutic range of 6–10 mg/L for mucosal healing. Results: Secondary LOR (reactive TDM) was the most common indication for TDM. These patients have consistently lower median IFX levels: 3.02 mg/L (IQR 1.14–6.67 mg/L) versus 5.22 mg/L (IQR 2.70–8.12 mg/L), P = 0.0001 compared with patients in remission (proactive TDM). TDM helped to identify unnecessary use of IFX in 30.6% of the TDM tests performed in luminal Crohn disease and ulcerative colitis patients, with an associated drug cost saving of $531.38 per IFX TDM test episode. Unnecessary IFX use was identified in 38.9% (96/247) of reactive IFX TDM tests performed and in 19.3% (35/181) of proactive testing. Conclusion: Use of both reactive and proactive IFX TDM is cost‐effective for IBD management as it informs the clinician where unnecessary use of IFX can be stopped.